Educação em mudanças climáticas : um estudo de caso em Passo Fundo, RS - Rocha, Vanessa Tibola da (2020)
The increase in the temperature of the Earth's surface has been worrying scientists, researchers, national and international government entities. This increase in global temperature boosts the effects of climate change resulting in extreme events. The Intergovernmental Panel on Climate Change (IPCC) warns that the planet continues showing a growth of 0.2ºC per decade. The forecast based on these projections is by the end of the 21st century the average global temperature of the planet could rise from 2ºC to more than 4ºC, if nothing will be done to reduce the increase in the Earth's temperature. In this sense, many ecosystems will be affected by the impacts of climate change. A necessary global alternative is people’s understanding of climate change focused on building resilience and tackling it. The objective of this study is to develop a model process of climate change education of teachers and students, in the municipality of Passo Fundo, in the Rio Grande do Sul state. The research methodology is exploratory, developed with a focus group (teachers and students of the sixth year of elementary school II) and without statistical representativeness, presenting a survey of primary data that characterizes the study as a ‘‘model for the climate change education process’’, which was structured in three phases: reflection, capacity and action. The results confirm that: 1) Climate change training and learning studies are incipient in many continents and from the last decade this topic has received the most attention; 2) The material developed by UNESCO, in 2014, has didactic-pedagogical potential for approaches related to climate change education (CCE). However, adaptations and changes are necessary given the different study realities; 3) Teachers and children represent groups of people with broad potential for local transformation. Therefore, there is a need to involve these groups in CCE process; 4) The CCE theme contributes to sustainable development since it has a multidisciplinary approach and it provides didactic-pedagogical approaches throughout the curriculum, addressing simple teaching and learning actions such as drawings, stories, posters, among others. Finally, it is concluded that there are still many actions to do regarding CCE since the theme requires further reflection in the theoretical and practical fields. Keywords: